2020
DOI: 10.1111/1749-4877.12477
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal microbiome of an Indo‐Pacific humpback dolphin (Sousa chinensis) stranded near the Pearl River Estuary, China

Abstract: The mammalian intestinal microbiome is critical for host health and disease resistance. However, the cetacean intestinal microbiota remains relatively unexplored. By using high-throughput 16S rRNA gene sequencing, we analyzed intestinal bacterial samples from an Indo-pacific humpback dolphin (Sousa chinensis) stranded near the Pearl River Estuary in China. The samples included 3 anatomical regions (foregut, midgut, and rectum) and 2 anatomical locations (content and mucus). Our analyses revealed that the dolph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 56 publications
(124 reference statements)
3
23
2
Order By: Relevance
“…Gut microbiota are likely shaped by diverse host factors, such as behavioral (i.e., social contact patterns), heritable (e.g., evolutionary history and genetics), and environmental (e.g., diet and geography; Kasper, 2014;Perofsky et al, 2019;Li et al, 2021;Wan et al, 2021). In this study, our results showed that the diversity of gut microbiota in L. edwardsi was significantly different from those of A. draco and N. confucianus, while the interspecific differences of the other three rodent species were not significant, which support our first hypothesis.…”
Section: Interspecific Variation On Gut Microbiota Between Rodent Spe...mentioning
confidence: 99%
“…Gut microbiota are likely shaped by diverse host factors, such as behavioral (i.e., social contact patterns), heritable (e.g., evolutionary history and genetics), and environmental (e.g., diet and geography; Kasper, 2014;Perofsky et al, 2019;Li et al, 2021;Wan et al, 2021). In this study, our results showed that the diversity of gut microbiota in L. edwardsi was significantly different from those of A. draco and N. confucianus, while the interspecific differences of the other three rodent species were not significant, which support our first hypothesis.…”
Section: Interspecific Variation On Gut Microbiota Between Rodent Spe...mentioning
confidence: 99%
“…Studies on the microbial diversity and composition in the gastrointestinal tracts of cetaceans are very few. To our knowledge, only 3 papers investigated the microbial communities in different regions of the gastrointestinal tracts in cetaceans (Wan et al 2018(Wan et al , 2020Tian et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Samples can be taken post-mortem [117] or under sedation [118]; however, there are obvious animal welfare implications for these, something that is especially relevant in studies of protected species. Opportunistic sampling from deceased individuals can be useful if internal sampling is of particular importance [119]. Scat sampling is an invaluable tool for sampling the gut microbiome as it is non-invasive and can, in many cases, be done without trapping or handling the host animal.…”
Section: Study Design Considerations and Sample Collectionmentioning
confidence: 99%
“…For example, cetaceans are incredibly hard to sample due to their vast ranges and the inaccessibility of many feeding grounds to researchers. As a result, many samples are opportunistically collected from necropsies of beached individuals [119,129]. This opportunistic sampling can be an excellent tool to supplement traditional sampling of wild populations and help overcome the challenges of small samples sizes.…”
Section: Sample Size Constraintsmentioning
confidence: 99%